UPAYA PENCEGAHAN DAN PENANGANAN HIPERTENSI MELALUI PENDEKATAN INTERPROFESIONAL COLABORATION PADA LANSIA DI DESA PUCANGAN KECAMATAN KARTASURA - Rizki Setiawan; Fitriya Ningsih; Rizka Salsabila Putri; Nafila Happy Qurrota'aini; Rindi Febriana; Khusnul Rohim Rufiana; Idha Rosydiana Fitri; Sisilia Hani Oktavira; Pristha Adilia Arga Putri; Ershela Putri Arnanda; Izzatul Arifah; Sulastri (Universitas Muhammadiyah Surakarta, 2024)
Hypertension is a manifestation of disturbances in the hemodynamic balance of the cardiovascular system, in which the pathophysiology is multi-factorial, so that it cannot be explained by only one single mechanism. One of the risk factors for hypertension is the poor level of knowledge and living habits of the elderly and their families. This IPE AIK KKN activity aims to increase the knowledge of the elderly by carrying out counseling activities regarding hypertension, nutrition counseling for hypertension sufferers, TTV examinations and providing demonstrations of anti-hypertension exercises. This service activity is carried out by several stages, namely the preparation (observation), implementation, and evaluation stages. The initial stage is carried out by checking blood pressure and asking questions in the form of a pre-test. The implementation phase is carried out by holding health education regarding hypertension by including definition material, how to prevent hypertension, diet for hypertension and how to control hypertension, after that it is continued with hypertension exercise. The final stage is an evaluation using a question and answer (post-test) to determine the level of understanding of the elderly after being given counseling. The pre-test results were relatively good, the mean was 74.44 and the post-test results were classified as good, 84.72. This activity was carried out smoothly and it can be concluded that the knowledge of the elderly increased after being given counseling on hypertension.